Aluminum oxide for photocatalytic organic transformations - Leow, Wan Ru (2017)
The use of sunlight to drive organic reactions constitutes a green and sustainable strategy for organic synthesis. In such reactions, the photoredox requirements of organic reactions are typically fulfilled through using wide band gap semiconductors or redesigning the photocatalyst. Herein, we demonstrated the use of a reverse strategy; instead of redesigning the dye as per convention, the reactant is chemisorbed on the Brønsted base sites of Al2O3 to form a surface complex, causing an upshift in its HOMO to a level accessible for electron abstraction by the dye. This enables the highly selective oxidation of benzylic alcohols to aldehydes by a large variety of dyes, even though negligible reaction occurred in the absence of Al2O3 or with other metal oxides. The charge-transfer surface complex formed between the dye and Al2O3 is also essential in facilitating the transport of electrons from BnOH to O2.